"Show Some Love": Youth and Teaching Artists Enacting Literary Presence and Musical Presence in an After-School Literacy-and-Songwriting Class. Issue 5 (May 2019) - Hess, Juliet; Watson, Vaughn W. M.; Deroo, Matthew R.
Background/Context: Youth's multiliteracies and musical practices are increasingly considered as taking place beyond school and including community-based educational contexts. Literacy scholars increasingly seek to understand the social and cultural contexts of literacy practices, underscoring youths' identities as present and future civic participants. Moreover, Small's concept of musicking reframes academic understandings of music to acknowledge the multiplicity of ways youth are inherently musical. Yet less is known about social and cultural contexts of multiliteracies practices and musicking activities of youth of color in community-based education settings. Moreover, less is understood about how youth demonstrate academic literacies and musicking activities, already present and informed by their lived experiences, and the formal curriculum of community-based educational contexts. This article examines the multiliteracies practices and musicking activities of youth of color during open mic at The Verses Project, a community-based literacy-and-songwriting class, to explore how youth demonstrate what Tatum and Muhammad referred to as "literary presence" and what we extend as youth's literary presence and musical presence. Purpose/Objective/Research Question/Focus of Study: This study1 details ways in which youth of color extended their literary and musical presence as active civic participants through engagement in open mic, in the context of a 15-week community-based literacy-and-songwriting class. In examining experiences of youth participants and teaching artists across open mic, we ask: What academic literacy practices and multifaceted musical activities already-present in youth's lived experiences do youth demonstrate during open-mic? And how do youth demonstrate literary presence and musical presence across literacy practices and musical activities? Setting: Data for this study were collected at the Community Music School—Detroit (CMS-D) during an after-school literacy-and-songwriting class for youth age 9 to 15. Research Design: Data for this 15-week qualitative study, informed by critical ethnography, were collected using videotaped observations, field notes, focus-group interviews, curriculum-planning meetings, multimodal artifacts, and researcher memos. Conclusions/Recommendations: This article shows how youth demonstrated uses of open mic, reflecting sharing as an act of bravery; teaching artists across open mic scaffolded youth's development of literary and musical presence; and youth, in words and music, across open mic, enacted already-present academic literacies and musicking activities. We discuss possibilities for using open mic in formal, school-based, English and music classrooms and extend the possibilities of theory, research, and teaching in literacy studies and music education that attend to the lived experiences of youths' literate and musical lives.